daun Daun Salam (Syzygium Polyanthum) Sebagai Penurun Kadar Kolesterol Dalam Darah - Aditya Ramadhon Islami Sakaganta; Asep Sukohar (CV. Jasa Sukses Abadi, 2021)
Coronary Heart Disease (CHD) is a major health problem in developed or developing countries. CHD is classified as a degenerative disease related to lifestyle, and socio-economic community. In 2008 it was estimated that 17.3 million deaths were caused by cardiovascular disease. The prevalence of hypercholesterolemia in Indonesia according to riset kesehatan dasar (riskesdas) in 2013 was obtained by Indonesians with higher than normal cholesterol levels higher in women by 39.6% when used with men by 30%. The full scientific bay leaf plant has the Latin name Eugenia polyantha Wight and has another scientific name, namely syzygium polyantha wight and eugenia lucidula miq. This plant belongs to the myrtaceae tribe. Bay leaf contains essential oils of 0.17%, citral, eugenol, tannin, flavonoids, and metal cavikol. Substances that are significant in lowering cholesterol are flavonoids and tannins. How flavonoids work in reducing cholesterol occurs when the hydroxyl group on cholesterol is considered with the ketone group on flavonoids forming hemiasetal. The carbonyl group in flavonoids will choose the hydroxyl group in cholesterol to determine the hydrogen bond. Tannins work quickly in binding and shrinking proteins. Tannin works as an antioxidant, astringent, and hypocholesterolemic. Tanninakan with mucous protein and intestinal epithelial cells so it needs to prevent fat.